2022
DOI: 10.1021/jacs.1c09916
|View full text |Cite
|
Sign up to set email alerts
|

True Reaction Sites on Discharge in Li–O2 Batteries

Abstract: In the pursuit of an advanced Li−O 2 battery, the true reaction sites in the cathode determined its cell performance and the catalyst design. When the first layer of insulating Li 2 O 2 solid is deposited on the electrode substrate during discharging, the following O 2 reduction to Li 2 O 2 could take place either at the electrode|Li 2 O 2 interface or at the Li 2 O 2 |electrolyte interface. The mechanism decides the strategies of catalyst design; however, it is still mysterious. Here, we used rotate ring-disk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Initial reports of redox mediation in lithium–oxygen systems included additives that helped in reversible charge–discharge chemistry in nonaqueous and aqueous electrolytes. , These are electron-transfer mediators. The ability to complex with oxygen and thus, increase oxygen solubility in the electrolyte, was soon identified as a desired feature in RMs. , Very recently, we demonstrated a proof-of-concept of the synergistic role of electron transfer and oxygen binding, by using the mammalian oxygen transporting protein hemoglobin, as an RM in lithium–oxygen batteries …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports of redox mediation in lithium–oxygen systems included additives that helped in reversible charge–discharge chemistry in nonaqueous and aqueous electrolytes. , These are electron-transfer mediators. The ability to complex with oxygen and thus, increase oxygen solubility in the electrolyte, was soon identified as a desired feature in RMs. , Very recently, we demonstrated a proof-of-concept of the synergistic role of electron transfer and oxygen binding, by using the mammalian oxygen transporting protein hemoglobin, as an RM in lithium–oxygen batteries …”
Section: Introductionmentioning
confidence: 99%
“…The ability to complex with oxygen and thus, increase oxygen solubility in the electrolyte, was soon identified as a desired feature in RMs. 10,11 Very recently, we demonstrated a proof-of-concept of the synergistic role of electron transfer and oxygen binding, by using the mammalian oxygen transporting protein hemoglobin, as an RM in lithium−oxygen batteries. 12 Structurally very similar to iron porphyrin (haem), iron phthalocyanine was the first reported organometallic redox mediator that also showed reversible oxygen shuttling ability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is the theoretical basis for the design of lithium-air batteries. 69 In addition to O 2 , there is also H 2 O in the air, and gases such as CO 2 and N 2 can also react with lithium. Therefore, if the air is directly introduced to participate in the reaction, LiOH, Li 2 CO 3 , and Li 3 N will also appear in the discharge products.…”
Section: Lithium Anodementioning
confidence: 99%
“…Similarly, it seems that CNTs pass through the Li 2 O 2 particles based on the SEM and transmission electron microscopy images of Shao-Horn et al The reaction interface is thus particularly important and is usually investigated by isotope-labeling techniques. Shen et al indicated that 75% of the active sites are at the electrode/Li 2 O 2 interface in the surface route . Lu et al suggested that new Li 2 O 2 is formed on the top (Li 2 O 2 /electrode interface) of toroidal Li 2 O 2 in the solution route .…”
mentioning
confidence: 99%
“…Shen et al indicated that 75% of the active sites are at the electrode/ Li 2 O 2 interface in the surface route 51. Lu et al suggested that new Li 2 O 2 is formed on the top (Li 2 O 2 /electrode interface) of toroidal Li 2 O 2 in the solution route.…”
mentioning
confidence: 99%